Scaffolding Online Interaction: EYL Teachers’ Perceptions and Attitudes during Covid-19 Pandemic Era - Rena Sylvia; Machdalena Vianty; Mgrt. Dinar Sitinjak (STAI Hubbulwathan Duri, 2022)
Scaffolding, a teacher’s act that provides adaptive assistance to young learners, is revealed to be effective in some studies. However, scaffolding in online learning is hardly visible. Therefore, this phenomenology study aims to discover the types of scaffolding used in online learning and what teachers’ perceptions and attitudes are towards it. In this study, English teachers from a primary school in Palembang, Indonesia, were chosen as participants. Data were collected using interviews, observation and field notes and were analysed into themes and constantly interpreted using Thematic Analysis. To check the research credibility, member checking was used. The findings claimed that scaffolding in online interaction is infiltrated into internet platforms containing virtual language exposure and collaborative learning where the virtual environment, communication, and brainstorming are crucial points for teachers to be considered in order to scaffold the English for EYL. Teachers are the main educators who assist them to reach lesson goals with cooperation of the parents’ participation in using technology and internet in this Covid-19 pandemic era.